Novel Approaches for Mucoadhesive Gel – A Review - Bhalerao, Madhuri; Shinde, Madhuri (Asian Journal of Pharmaceutical Research and Development, 2013)
Mucoadhesion can be defined as a state in which two components, of which one is of biological origin, are held together for extended periods of time by the help of interfacial forces. Mucoadhesive drug delivery systems is one of the most important novel drug delivery systems with its various advantages and it has a lot of potential in formulating dosage forms for various diseases and has controlled release of drug delivery system. Drug actions can be improved by developing new drug delivery systems, such as the mucoadhesive drug delivery system. These systems remain in close contact with the absorption tissue, the mucous membrane and release the drug at the action site leading to increase the bioavailability of drug and both local and systemic effects. So, carrier technology offers a novel approach for drug delivery by coupling the drug to a carrier particle such as microsphere, nanoparticle, liposome, etc. which modulates the release and absorption characteristics of the drug. Hence, the discussion focus on physiology of mucus, mucoadhesive dosage forms, and novel methods for mucoadhesive gel such as microemulsion, liposomal, microspheres based gel and their evaluation techniques.